Application of fenitrothion on Heteropneustes fossilis causes alteration in morphology of erythrocytes via modifying hematological parameters. (2022) - Ritu, Rifat Farjana; Islam, SM Majharul; Rashid, Harunur; Haque, Shahroz Mahean; Zulfahmi, Ilham; Sumon, Kizar Ahmed
Abstract: In Bangladesh, the extensive use of fenitrothion on crops and in aquaculture ponds inevitably threatens a range of aquaculture species, including fish, owing to stress responses and physiological disturbances. The present study elucidated the potential toxic effects of fenitrothion on the blood biomarkers (haemato-biochemistry and structure of erythrocytes) of stinging catfish ( Heteropneustes fossilis ), a commercially significant aquaculture species. Fish were exposed to four sub-lethal concentrations (0%, 10%, 20%, and 40% of the 96-h LC50 value) of fenitrothion in triplicate and observed on the 7th, 14th, 21st, and 28th day following exposure. With increasing fenitrothion concentration, blood glucose and white blood cell levels increased significantly; in contrast, hemoglobin, red blood cell, and packed cell volume substantially decreased. However, the mean corpuscular volume and mean corpuscular hemoglobin did not change significantly during the exordial period (0–7 d); although, at a later stage, changes were observed. Frequencies of observed erythrocytic nuclear abnormalities, such as degeneration, bi-nucleus, micronucleus, notch nucleus, and nuclear bridge and erythrocytic cellular abnormalities, such as echinocytes, fusion, elongation, and tear drop morphology increased significantly in a concentration-dependent manner. Differences between the control individuals and those individuals under treatment were considered insignificant for twin cells on the 14th day of exposure. The study showed the pernicious impact of the effects of fenitrothion on H. fossilis through physiological alteration, which is likely to pose challenges for aquaculture production. Graphical Abstract: ga1 Highlights: Stinging catfish is highly prone to fenitrothion used in croplands and fish ponds. The 96-h LC50 of fenitrothion for stinging catfish was 8.3 mg/L. Blood glucose and white blood cell increased significantly. Hemoglobin, red blood cell and packed cell volume significantly decreased. Exposure to fenitrothion resulted in abnormalities of erythrocyte structure.